Effects of CTGF blockade on attenuation and reversal of radiation-induced pulmonary fibrosis - Bickelhaupt, Sebastian; Erbel, Christian; Timke, Carmen; Wirkner, Ute; Dadrich, Monika; Flechsig, Paul; Tietz, Alexandra; Pföhler, Johanna; Gross, Wolfgang; Peschke, Peter; Hoeltgen, Line; Katus, Hugo; et al. (Journal of the National Cancer Institute, 2017)
Abstract. Background: Radiotherapy is a mainstay for the treatment of lung cancer that can induce pneumonitis or pulmonary fibrosis. The matricellular protein